2020
DOI: 10.1128/mbio.02971-19
|View full text |Cite
|
Sign up to set email alerts
|

Development of Candida auris Short Tandem Repeat Typing and Its Application to a Global Collection of Isolates

Abstract: Candida auris is a pathogenic yeast that causes invasive infections with high mortality. Infections most often occur in intensive care units of health care facilities. It is crucial to trace the source and prevent further spread of C. auris during an outbreak setting; therefore, genotyping of C. auris is required. To enable fast and cost-effective genotyping, we developed a short tandem repeat (STR) typing assay for C. auris. STRs in C. auris were identified, and from an initial selection of 23 STRs, 12 were u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 36 publications
1
70
0
Order By: Relevance
“…Candida auris is currently separated into five geographically restricted clades (East-Asia, South-Asia, Africa, Iran and South-America) [ 38 ]. In the present study, we typed 55 isolates, originating from India, Kuwait, Oman, South-Africa, Japan, Korea, Venezuela and Iran with STR genotyping [ 39 ], which showed that the Omani isolates belong to the South Asian clade and had a clonal nature. STR genotyping also agreed completely with a previous whole genome analysis study on C. auris [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Candida auris is currently separated into five geographically restricted clades (East-Asia, South-Asia, Africa, Iran and South-America) [ 38 ]. In the present study, we typed 55 isolates, originating from India, Kuwait, Oman, South-Africa, Japan, Korea, Venezuela and Iran with STR genotyping [ 39 ], which showed that the Omani isolates belong to the South Asian clade and had a clonal nature. STR genotyping also agreed completely with a previous whole genome analysis study on C. auris [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…For genotyping C. auris, microsatellite analysis was employed using the following reference strains of clade I (India: ARbank 389), clade II (Japan: ARbank 381), clade III (South Africa: ARbank 383), clade IV (Venezuela: B11245, B11247, B11243, B11244, B1124) and clade V (Iran: ARbank 1097 = IFRC 2087) [ 39 ]. Briefly, DNA was extracted and purified with the MagNA Pure LC instrument and the MagNA Pure DNA isolation kit III (Roche Diagnostics GmbH, Mannheim, Germany), according to the recommendations of the manufacturer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A new report in mBio by de Groot et al describes the development of an STR typing approach for Candida auris (10). STR markers were initially identified from a search across reference genome assemblies generated for each of the initially described four major clades (11).…”
mentioning
confidence: 99%
“…[38][39][40] Recently, a novel MLMT typing for Candida auris showed that the technique is highly concordant with whole genome sequencing in identifying five different geographical clusters in C auris. 41 However, due to the lack of a MLMT global database as compared to MLST the former is not well acknowledged in genotyping of C neoformans.…”
Section: Discussionmentioning
confidence: 99%